2015
DOI: 10.1111/jgs.13507
|View full text |Cite
|
Sign up to set email alerts
|

Technology Use and Frequency and Self‐Rated Skills: A Survey of Community‐Dwelling Older Adults

Abstract: Many older adults are using technology regularly, but the vast majority still rate their technology skills as poor or average,reflecting their low usage of less-familiar items such as tablet computers. Despite moves toward increasing the use of ICT in the care, rehabilitation, and monitoring of older adults, baseline use of such devices is low. Further study is required to investigate how people's attitudes toward and experience with ICT influence its utility in clinical practice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 6 publications
3
11
1
Order By: Relevance
“…The low rates (22 %) of game-experience seen in our study population are comparable to the results of Scanlon et al [ 17 ], who reported that only 3 % of their investigated cohort used a game console. This option for delivering CR is thus certainly subject for further research.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The low rates (22 %) of game-experience seen in our study population are comparable to the results of Scanlon et al [ 17 ], who reported that only 3 % of their investigated cohort used a game console. This option for delivering CR is thus certainly subject for further research.…”
Section: Discussionsupporting
confidence: 89%
“…Concerning mobile phone use, with 97 % mobile phone and 64 % smartphone ownership, our study is in line with the findings from Dale et al [ 11 ] who also studied CR patients. Similarly, in the older population in general, mobile phones and smartphones are used by the vast majority of men and women [ 13 , 14 , 17 ]. Despite the widespread use of smartphones in our population, current interest in a smartphone App for CR support was lower compared to interest in internet based CR support.…”
Section: Discussionmentioning
confidence: 99%
“…The review found these type of technologies to be feasible for patients and reliable for mental health domains assessment within the geriatric population. ( 24 ) Despite the fact that 76% of community-dwelling older adults rated their technology skills as poor or average in a recent survey, ( 13 ) geriatric patients in our study expressed being interested in using iPad-based symptom self-report questionnaires once they were routinely available in future clinical practice.…”
Section: Discussionmentioning
confidence: 79%
“…This is particularly important in patients with severe late-life mental illness, who are often even less exposed to tablet computer and related technologies. ( 13 ) This study aimed to compare the usability and acceptability of tablet computers vs. traditional paper forms in completing self-report questionnaires in late-life mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional services like the Geriatric Day Hospital could be leveraged to this new purpose by providing a “hub” to assist and supervise this for appropriate patients rather than require the building of new and likely commercial infrastructure, which may not have the means or interest to serve this distinct and specialized group. Given that older adults attending a Geriatric Day Hospital in Ireland rated their experience with ICT as limited ( 41 ), eHealth literacy would also need to be fostered in this setting. This is echoed by evidence that a supportive environment attuned to the needs of older adults is required for them to effectively use ICT ( 42 ).…”
mentioning
confidence: 99%